Fueling the revolution: social media’s effect on societal revolutions - Khomko, Marta Maria (2016)
“When we change the way we communicate, we change society”- Clay Shirky. The rise of social networking sites will play an increasingly important role in the formation of group identity and collective actions such as societal protests and Revolutions. The new use of social networking sites is a significant departure from static, solely profile based online platforms. Networks such as Facebook, Twitter, etc. are being utilized by thousands of individuals in an organized fashion to incite real social change. The topic of this dissertation is social media’s effect on social Revolutions. It focuses more specifically on the Ukrainian Revolution as it has received considerable attention and interest. For this reason this topic will be looked at from a marketing perspective to analyze how social media dispenses information and influences individuals to engage with the movement. Drawing from McLuhan’s media theory, social network and collective action theories, this dissertation argues that social networking sites impact societal revolutions by influencing protest attendance and information perception.